Sports Education Learning Program Evaluation In Senior High School - Handayani Nila Praja; Rivo Panji Yudha (STKIP Muhammadiyah Kuningan, 2021)
This study aims to evaluate the high school level sports education learning program. In conducting the study, the evaluation involved the CIPP model. Then, the research informants consisted of the principal, the vice-principal, 2 Sports Education teachers, and 10 students from each class X, Class XI, and Class XII. Data collection was carried out by interview, observation, and documentation. The data analysis technique used descriptive qualitative analysis. Based on the research results and discussion of the evaluation of the Physical Education learning plan for SMA Negeri 1 Babakan in the study, it can be concluded that the learning program of SMA Negeri 1 Babakan was carried out well, with an average score of 83.5%. Learning Assessment and Learning Management has reached 59.25 or 78.00% and is included in the